Mémoire présenté au Comité permanent des Finances relativement au remplacement de la TPS - Lanteigne, Pierre (Assurances, 1994)
The "Submission to the Standing Committee on Finance on the matter of replacing the GST" has been presented on March 23, 1994. lnsurance brokers, particularly Canadian-owned insurance brokers, bear a clearly excessive and inequitable burden of GST. The new sales tax environment to be defined by the federal government should place brokers on an equal footing with companies that render professional services to their clients such as legal, accounting and engineering firms. As is the case for these firms, the value added brokers provide basically lies in the quality of their counsel; brokers sell the time and expertise of their personnel. The fact that they provide this service in conjunction with a product sold on behalf of insurers should not cause them to be singled out among other service companies for GST purposes. Regardless of the solution chosen, the current treatment of insurance brokers under the GST must be rectified by the federal government in keeping with its promise to replace the GST. Sodarcan is prepared to discuss with the members of the Finance Committee and the representatives of the Minister of Finance any sales tax alternatives that would treat our industry more equitably.